2019
DOI: 10.1007/978-3-030-18400-1_47
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Analysis of the Implementation of Health Information Systems for Public Healthcare Service Delivery in Resource-Constrained Environments: A South African Study

Abstract: The use of technological solutions is argued to offer quality enhancing efficiencies in the delivery process of healthcare services. For this to be realized certain objectives of these technological solutions have to be achieved. The public health system in South Africa faces various challenges such as poor coordination of most technological solutions therefore fragmented; a lack of interoperability between different systems, haphazard procurement processes and poor information management capabilities. The arg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The review identified 12 articles that discuss challenges with the current implementation of HISs. 15,43 The challenges include lack of standardisation, poor interoperability, inadequate coordination and fragmentation of data. In addition, socio-economic and technical factors shaped by broader organisational factors further exacerbate these challenges.…”
Section: Results and Analysismentioning
confidence: 99%
“…The review identified 12 articles that discuss challenges with the current implementation of HISs. 15,43 The challenges include lack of standardisation, poor interoperability, inadequate coordination and fragmentation of data. In addition, socio-economic and technical factors shaped by broader organisational factors further exacerbate these challenges.…”
Section: Results and Analysismentioning
confidence: 99%